Recent progress of electrolytes for Mg-air batteries: A review - Shubo Li; Xuening Li; Chenchen Zhao; Hongxing Liang; Ke Liu; Xian Du; Wenbo Du (Journal of Magnesium and Alloys)
Mg-air batteries, with their high theoretical energy density, low cost, and eco-friendliness, offer broad application prospects. Nonetheless, challenges such as corrosion, uneven dissolution of the Mg anode, and the adherence of discharge products impair the utilization efficiency of Mg anodes and reduce the output voltage of these batteries. The electrolyte plays a pivotal role in the interface structure and electrode reactions within Mg-air batteries, directly affecting their performance. This review focuses on the latest advancements in electrolytes for Mg-air batteries, covering various aspects including aqueous electrolytes and their additives, non-aqueous electrolytes, as well as electrolytes for rechargeable Mg-air batteries, elucidating the underlying mechanisms. In addition, potential avenues for future research in Mg-air battery electrolytes are outlined, providing a comprehensive perspective on the development of high-performance Mg-air batteries.